2022
DOI: 10.1186/s40798-022-00507-x
|View full text |Cite
|
Sign up to set email alerts
|

Total Sedentary Time and Cognitive Function in Middle-Aged and Older Adults: A Systematic Review and Meta-analysis

Abstract: Background An estimated 47 million people have dementia globally, and around 10 million new cases are diagnosed each year. Many lifestyle factors have been linked to cognitive impairment; one emerging modifiable lifestyle factor is sedentary time. Objective To conduct a systematic review and meta-analysis of peer-reviewed literature examining the association between total sedentary time with cognitive function in middle-aged and older adults under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Given that both MVPA and SB were both fairly high, but only MVPA showed a relationship with neural activation, our results should be treated with caution since it is plausible that the task performed did not appropriately capture executive control associated with SB. However, it is worth noting that the association between SB and executive function appears to be substantially weaker than the association between MVPA and executive function 25 , 26 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Given that both MVPA and SB were both fairly high, but only MVPA showed a relationship with neural activation, our results should be treated with caution since it is plausible that the task performed did not appropriately capture executive control associated with SB. However, it is worth noting that the association between SB and executive function appears to be substantially weaker than the association between MVPA and executive function 25 , 26 .…”
Section: Discussionmentioning
confidence: 89%
“…MVPA and SB share a bidirectional relationship with executive control performance—whereby greater MVPA and less SB predict better performance, and vice versa 22 24 . However, the association between SB and executive function appears to be substantially weaker than the association between MVPA and executive function 25 , 26 .…”
Section: Introductionmentioning
confidence: 78%
“…In this work, physical activity tends to be included as one factor among a list of behavioral and clinical risk factors and tends to be measured with a broad overall measure of activity. Research on physical activity and episodic memory in particular has shown that more engagement in physical activity is associated with better episodic memory (Stenling et al, 2022), whereas the relation between sedentary behavior and episodic memory is more mixed (Dillon et al, 2022). Given that physical activity is dynamic, and that activity fragmentation has been associated with aspects of cognitive health, such as cognitive complaints and impairment (e.g., Del Pozo Cruz & Del Pozo-Cruz, 2021;Wanigatunga, Liu, et al, 2022), a more nuanced approach to patterns of physical activity may help better identify how purpose is associated with better cognitive function, such as episodic memory.…”
Section: Purpose and Activitymentioning
confidence: 99%
“…In older adults, physical activity benefits cognitive performance, is associated with a lower risk of dementia, and is beneficial to cognitive impairments in those with dementia [2], while measures of sleep are associated with memory and executive function [20]. There is some evidence of associations of sedentary time and cognitive function in this age group, but findings have been more variable than for physical activity and sleep [21]. Although there has been some support of beneficial associations between physical activity and cognitive measures (and, to some extent, adverse associations with high sedentary time), a lack of sufficient studies limits the conclusions that could be drawn for children under 6 years of age in the 2018 Physical Activity Guidelines Advisory Committee Scientific Report [2].…”
Section: Introductionmentioning
confidence: 99%